EFEITO DE DIFERENTES FORMULAÇÕES DE NPK NOS CARACTERES DE PRODUÇÃO E QUALIDADE DE CANA-DE-AÇÚCAR - Wentz, Renan; Bernardes, Diego; Quadros, Valmir J. d.; Kalb, Marcos A.; Stasiak, Mauricio; Rolim, Odair; Boff, Jose T.; Uhde, Leonir T.; Silva, Jose A. G. d.; Schwertner, Diogo V. (Salão do Conhecimento, 2013)
Resumo